Downregulation of transcription factor GATA4 sensitizes human hepatoblastoma cells to doxorubicin-induced apoptosis - Tea Soini; Marjut Pihlajoki; Antti Kyrönlahti; Leif C Andersson; David B Wilson; Markku Heikinheimo (Tumor Biology)
Hepatoblastoma, the most common type of pediatric liver cancer, is treated with a combination of surgery and chemotherapy. An essential drug in the treatment of hepatoblastoma is doxorubicin, which in high doses is cardiotoxic. This adverse effect is due to downregulation of cardiac expression of transcription factor GATA4, leading in turn to diminished levels of anti-apoptotic BCL2 (B-cell lymphoma 2) protein family members. GATA4 is also expressed in early fetal liver, but absent from normal postnatal hepatocytes. However, GATA4 is highly expressed in hepatoblastoma tissue. In this study, we assessed the role of GATA4 in doxorubicin-induced apoptosis of hepatoblastoma cells. Herein, we demonstrate that doxorubicin decreases GATA4 expression and alters the expression pattern of BCL2 family members, most profoundly that of BCL2 and BAK, in the HUH6 hepatoblastoma cell line. Silencing of GATA4 by siRNA prior to doxorubicin treatment sensitizes HUH6 cells to the apoptotic effect of this drug by further shifting the balance of BCL2 family members to the pro-apoptotic direction. Specifically, expression levels of anti-apoptotic BCL2 were decreased and pro-apoptotic BID were increased after GATA4 silencing. On the whole, our results indicate that since high endogenous levels of transcription factor GATA4 likely protect hepatoblastoma cells from doxorubicin-induced apoptosis, these cells can be rendered more sensitive to the drug by downregulation of GATA4.